Zoledronic Acid in Osteoporotic Vertebral Compression Fractures Treated With Percutaneous Kyphoplasty: A Meta-Analysis - Tian, Peng; Liu, Yue; Li, Zhi-jun; Xu, Gui-jun; Ma, Xin-long (Frontiers in Surgery, 2021)
Background We performed a meta-analysis to evaluate the efficacy and safety of zoledronic acid combined with percutaneous kyphoplasty (PKP) in treating osteoporotic vertebral compression fractures (OVCFs). Methods Eligible scientific articles published prior to July 2020 were retrieved from the PubMed, Springer, ScienceDirect and Cochrane Library databases. The statistical analysis was performed with RevMan 5.1. Results Three randomized controlled trials (RCTs) and 2 non-RCTs met the inclusion criteria. The present meta-analysis revealed that zoledronic acid combined with PKP is associated with a higher BMD, a better quality of life, less severe low back pain, and fewer additional vertebral body fractures than is percutaneous vertebral augmentation alone. Conclusions Compared with PKP only, zoledronic acid combined with percutaneous vertebral augmentation is beneficial for OVCFs.